Cryopreservation of lipoaspirates: in vitro measurement of the viability of adipose‐derived stem cell and lipid peroxidation. Issue 5 (11th May 2020) - Kim, Dong Yeon; Kim, Eunjin; Kim, Ki Joo; Jun, Young‐Joon; Rhie, Jong‐Won
Abstract: As the storage time of the fat tissue passes by, lipid peroxidation and creation of by‐products may take place. The objective of this study was to evaluate the cell viability and functional changes of adipose‐derived stem cells (ADSCs) in the cryopreserved lipoaspirates at different temperatures in accordance with lipid peroxidation. Lipoaspirates acquired from liposuction were divided into four different temperature groups and stored at 4°C, −20°C, −80°C, and −196°C. After isolating ADSC from each sample, gross cell morphology and cell viability were compared with doubling time and colony‐forming unit (CFU) formation ability. Acid value, that is, thiobarbituric acid value was measured to assess lipid peroxidation. No viable ADSC was observed in −20°C and −196°C samples for past 1 week and a superior number of the live cells were detected in the 4°C group compared with the −80°C group. However, the persistence of cell division and CFU formation after 1 week was only observed in adipocytes stored at −80°C. Lipid peroxidation mainly occurred at 4°C and −20°C storage samples. If the lipoaspirates were planned to be cryopreserved, it is advised to store at −80°C. However, the number of actually functional ADSCs is very low. Furthermore, even in the cryopreserved status, continuous lipid peroxidation and by‐product creation took place, suggesting shorter preservation period as possible in the clinics.